2009
DOI: 10.1007/s10162-009-0180-0
|View full text |Cite
|
Sign up to set email alerts
|

On- and Off-Frequency Forward Masking by Schroeder-Phase Complexes

Abstract: Forward masking by harmonic tone complexes was measured for on-and off-frequency maskers as a function of masker phase curvature for two masker durations (30 and 200 ms). For the lowest signal frequency (1 kHz), the results matched predictions based on the expected interactions between the phase curvature and amplitude compression of peripheral auditory filtering. For the higher signal frequencies (2 and 6 kHz), the data increasingly departed from predictions in two respects. First, the effects of the masker p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 46 publications
4
29
1
Order By: Relevance
“…The MOCR has an onset delay of about 25 ms (Backus and Guinan, 2006). Wojtczak and Oxenham (2009) reported that the differences they found in forward masking between long and short maskers can be explained by a model incorporating MOCR-controlled gain reduction. Jennings et al (2009) found some indications that the presence of a precursor stimulus preceding a 20-ms forward masker reduces the cochlear gain.…”
Section: B Multiple Maskersmentioning
confidence: 96%
See 1 more Smart Citation
“…The MOCR has an onset delay of about 25 ms (Backus and Guinan, 2006). Wojtczak and Oxenham (2009) reported that the differences they found in forward masking between long and short maskers can be explained by a model incorporating MOCR-controlled gain reduction. Jennings et al (2009) found some indications that the presence of a precursor stimulus preceding a 20-ms forward masker reduces the cochlear gain.…”
Section: B Multiple Maskersmentioning
confidence: 96%
“…Assuming that the BM is more compressive without activation of the MOCR, it can be hypothesized that excess masking is stronger for a Gaussian masker than for longer maskers. Indeed, the results of some recent nonsimultaneous masking experiments suggest the importance of the masker duration by means of the effect of the MOCR on cochlear compression (Jennings et al, 2009;Wojtczak and Oxenham, 2009;Plack and Arifianto, 2010). One goal of the present study was to measure masking additivity for very short Gaussian maskers to rule out the influence of the MOCR and to compare the results with those from the literature for different maskers which might have involved MOCR effects.…”
Section: Introductionmentioning
confidence: 92%
“…A recent study (Wojtczak and Oxenham, 2009) showed that the combination of compression and negative curvature was in some cases insufficient to explain phase effects observed in forward masking conditions. They suggested a more complex picture in which the medial olivo-cochlear reflex could modulate the non-linearity of the BM depending on the spectral region and the masker duration.…”
Section: Introductionmentioning
confidence: 99%
“…Our second finding shows that the occluder had similar effects on the continuity illusion and forward masking. Based on the notion that forward masking depends primarily on the long-term internal excitation evoked by the masker (Carlyon and Datta 1997b ; Wojtczak and Oxenham 2009), this suggests that the illusion depends on a neural representation of the average excitation evoked by the occluder—possibly related to the specific loudness of the occluder, i.e., its loudness within the critical band centered on the frequency of the target sound (Mauermann and Hohmann 2007). …”
Section: Discussionmentioning
confidence: 99%